Design of a millimeter‐wave wideband bandpass filter with novel‐slotted substrate integrated waveguide. Issue 10 (27th July 2016) - Dong, Kaida; Mo, Jingyan; He, Yuhong; Ma, Zhewang; Yang, Xuexia
ABSTRACT: A millimeter‐wave (mmW) wideband band‐pass filter (WBF) is proposed and designed by using novel‐slotted unites etched on the metal planes of SIW cavities in this paper. The novel‐slotted SIW cavity consists of two pairs of same size dumbbell slots etched on both the top and bottom metal planes of the SIW, which acts as a shunt resonator. And there is 90‐degree angle rotated between the novel‐slotted unites on top and bottom planes. The novel‐slotted SIW unit can be used to control the transmission zero and the cutoff frequency at upside. Finally, a five‐order millimeter‐wave wideband band‐pass filter is proposed and fabricated. The measured results show that the filter achieves insertion loss of −1.54 dB at 32.5 GHz, return loss of better than 12.5dB and 3dB fractional bandwidth (FBW) of 34.6%. A good agreement between simulated and measured results verifies the validity of this design methodology. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2406–2410, 2016